PERSEPSI PETANI TERHADAP INOVASI PRODUKSI UMBI MINI BAWANNG MERAH ASAL BIJI (TRUE SEED OF SHALLOT/TSS) RAMAH LINGKUNGAN DI KABUPATEN GROBOGAN - Mardiyanto, Tri Cahyo; Pangestuti, Retno; Prayudi, Bambang; Endrasari, Retno (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2017)
The study aims to determine the perception of farmers towards innovation small tuber onion production from seeds (TSS) environmentally friendly in Grobogan. The study was conducted in July 2015 in the village of Brabo, District Tanggungharjo, Grobogan. Respondents in the sample taken intentionally (purposive sampling) of the onion farmers in Tanggungharjo, Penawangan, Klambu, and Godong District with totaling 30 farmers. Data taken include respondent characteristic, relative advantages of innovation, compatibility, complexity, tribality and observability. Data were analysed descriptively. The results showed that most respondents have aged between 38-47 years old, the level of high school education, and old farm between 3-12 years. In general, the perception of farmers towards innovation small tuber onion production from seeds (TSS) environmentally friendly in Grobogan were high, so it deserves to be disseminated to farmers through a system integration approach of the group.